2016
DOI: 10.1155/2016/5347262
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dapagliflozin on Glycemic Variations in Patients with Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: Objectives. To observe changes in blood glycemic variations and oxidative stress level before and after dapagliflozin treatment in patients with newly diagnosed T2DM. Methods. This was a randomized, double-blind, placebo-controlled, phase 3 trial. A total of 28 patients with newly diagnosed T2DM with HbA1c levels of 7.5–10.5% were randomly selected to receive dapagliflozin or placebo treatment for 24 weeks. After baseline data were collected, we analyzed glycemic variations and plasma 8-iso PGF2α level at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
2
27
0
4
Order By: Relevance
“…14,15 Dapagliflozin is an orally administered, potent and selective inhibitor of SGLT2 that significantly reduces blood glucose levels and improves glycaemic variability. 16 Dapagliflozin is approved for the treatment of T2DM and has been shown to improve glycaemic control, stabilize insulin dosages and reduce body weight with low rates of hypoglycaemia. [17][18][19][20][21][22] When assessing dapagliflozin in patients with T1DM, the pharmacokinetic profile is dose-dependent and similar across Japanese 23 and Caucasian 24 patients.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Dapagliflozin is an orally administered, potent and selective inhibitor of SGLT2 that significantly reduces blood glucose levels and improves glycaemic variability. 16 Dapagliflozin is approved for the treatment of T2DM and has been shown to improve glycaemic control, stabilize insulin dosages and reduce body weight with low rates of hypoglycaemia. [17][18][19][20][21][22] When assessing dapagliflozin in patients with T1DM, the pharmacokinetic profile is dose-dependent and similar across Japanese 23 and Caucasian 24 patients.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes, oxidative stress plays a key role in favouring the appearance of cardiovascular complications (21). In patients with type 2 diabetes, dapagli ozin reduced glucose variability as well as oxidative stress (22), while it has been reported in an animal model of diabetes that empagli ozin can reduce oxidative stress generation (23). Therefore, although not detected in our analyses, we believe that the role of reducing HbA1c variability in the bene cial effects of empagli ozin on cardiovascular death remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed a beneficial effect of dapagliflozin monotherapy on the reduction of diurnal glycaemic variability, assessed as the mean amplitude of glucose fluctuations, and the reduction of oxidative stress, assessed by plasma 8-prostaglandin F2a levels [17]. It was also found in 4 week-observation that dapagliflozin in combination with metformin or with insulin reduces the mean amplitude of glucose fluctuations by 10 mg/dL, whereas in patients receiving placebo in combination with metformin or with insulin, the mean fluctuation amplitude increased by 5.3 mg/dL [18].…”
Section: Hyperglycaemia and Diurnal Variations Of Blood Glucosementioning
confidence: 99%